Annotation and Commentary in the Modernist Edition: A Critique. Issue 1 (February 2020) - Mierlo, Wim Van
Abstract : Annotation and commentary have been little considered in discussions about scholarly editing, despite being some of the most used segments of the scholarly edition. What treatments do exist mostly focus on practical aspects about the quality and style of annotation. This essay analyses some of the theoretical assumptions that underlie annotational practices with specific reference to the editing of modernist works. It puts into question, first of all, some common perceptions about annotation, which is sometimes viewed as interfering with the readerly experience, to address the matter of the reader: what kind of reader are annotations for? Because annotations are a contextual and hermeneutic device to bridge the gap between the literary work that has come to us from the past and the reader's present, not all readers are served by a single style of annotation. Conversely, to accept this hermeneutic value also means that annotation is never neutral or objective; while editorial practices tend to avoid open interpretive annotation, annotations nonetheless direct the process of reading and interpretation. Annotation thus participates in the sense-making process and, like all other editorial interventions, it represents an act of mediation.